Żydowskie szkolnictwo podstawowe, średnie i zawodowe w okresie II Rzeczypospolitej Polskiej ze szczególnym uwzględnieniem Krakowa (Krzysztofory. Zeszyty Naukowe Muzeum Historycznego Miasta Krakowa, 2026)
JEWISH PRIMARY, SECONDARY AND VOCATIONAL SCHOOLS DURING THE SECOND REPUBLIC OF POLAND, WITH SPECIAL ATTENTION TO CRACOWThe aim of this article is to acquiant the reader with the Jewish school system of 1918-1939.Used in this article were mainly archival materials in the the Archives of the Polish Academy of Science in Cracow, Official Journals of the Ministry of Religions and Public Enlightment, school statistics of the Central Statistics Office, Cracow school reports and articles published in Alamanach Szkolnictwa Żydowskiego w Polsce (Almanach of Jewish Schools in Poland), the Nowy Dziennik (New Journal), the Głos Gminy Żydowskiej (Voice of the Jewish Congragation), the Sprawy Narodowościowe (Nationality Matters), the Biuletyn ZIH (Bulletin of the Jewish Historical Institute) and the Miesięcznik Żydowski (the Jewish Monthly).For clarity, the collected material has been divided into three sections:—first, a brief characterization of the Jews who lived in Poland;—second, the whole of the Jewish school system, divided into traditional schools, elementary lay schools, and secondary and vocational schools; — third section is devoted to Jewish schools in Cracow divided into public elementary schools, private elementary schools without public rights, and high and vocational schools.I.Reborn Poland was a multinational state in which one third of the population were national minorities. The Jews were one of the most populous groups, second largest among the national minorities. During the period of the Partitions of Poland between three occupying nations, they were subject to various political and administrative influences, which were clearly reflected in the language they used in everyday life (Russian, German, Polish), but the common „Jewish language” was Yiddish with local loan-words. As a consequence, the multitude of languages was sure to cause disputes, and with time to sharp struggle for the national language.Another problem was that the Jews were dispersed all over Poland and nowhere were they the majority of the local population. They were associated in independent and equal religious congregations and were not subject to any higher authorities.The Jews who lived in small towns and villages remained faithful to their own culture and religion, and the main regulations of the Jewish community were the commandments included in the holy books; in contrast, in large cities, the abandonment of tradition and the secularization of the Jewish community was very clear at that time.II.Traditional schools — heders, Talmud Torahs, reformed heders, yeshivas and Bet-Yakov schools.Boys went to heders from the age of five, and every Jewish child had access to learning no matter what property status their parents enjoyed. Heders and Talmud Torahs in small towns and villages did not teach secular knowledge, and for that reason the children who attended them had to be taught general subjects in public elementary schools. This was a big problem, considering that about 25% of the Jews lived in towns and villages in which the teaching and education of children were limited to heders. In the first years after the war, an additional difficulty was the lack of a uniform school administration in the land incorporated into the Polish state. At last, the situation was significantly improved after the issuance of the decree „On Obligatory School Attendance”, in force all over Poland form the school year 1922/23.Pursuant to the decree, Jewish children who were students at religious schools were obliged to attend public schools, with an option to complete their religious education at heders. That way, heders would have lost the importance they had thus far, and the Jewish children would be under the undivided influence of the public school. Because the Central Organization of Orthodox Jews which supervised all religious schools did not want that to happen, it began a broad campaign for so-called reformed heders, incorporating secular subjects in their curriculums.The matter was finally settled by the Law on Private Schools and Teaching and Educational Institutions of March 11, 1932. These same traditional and orthodox religious schools which kept the old teaching and educational patterns were to be the places where hundreds thousands of Jewish children were taught. Schools of such kind, exclusively for boys, were everywhere were Jews lived. They came to be under the Horev Central Educational Organization which supervised all heders, Talmud Torahs and yeshivas for older boys; the goal of these schools was to educate more apt students as rabbis, religious judges, religion teachers and Talmud students.In 1920 Tahkemoni Jewish college was created in Warsaw to teach official rabbis; it taught its students religion and moral as well as secular knowledge according to the high school curriculum. Other yeshivas were organized mostly in central and eastern Poland; they were less frequent in southern Poland. Such schools also included schools for girls, called Bet Yakov, whose aim was to educate girls in both a religious and a national spirit. Teaching staff for such schools was trained in a teachers’ college established in Cracow in 1925.Among religious schools, the Yeshivat Hanai theological university, for about 500 students, founded in Lvov in 1924, had an important role.Secular elementary schools: Yiddish, Hebrew/national and bilinguial.Secular Jewish schools teaching in Yiddish could be found all over the country, but they were the most frequent in the Warsaw, Wilno and Łódź districts.In March 1921 a conference of organizations supporting Yiddisz Jewish schools was held in Warsaw, with the participation of about 600 delegates, at which the Central Yiddish School Organization (CISZO) was brought to life. Promotors of such schools had, apart from general ideas on secular schooling, some socialist ideas. However, Yiddish schooling did not find support from the Jewish community. Religious parents considered a school without religion the worst of evils, while the Jewish intelligentsia did not accept the proletarian character of the school.A characteristic feature of the CISZO schools was that girls were in the great majority; they were 2/3 of the total number of students in elementary schools, preschools and secondary schools alike. Schools of such kind were created mainly in the Białystok and Wilno voivodeships.Apart from the traditionally religious type and the Yiddish type of schools, there was also the Hebrew national type, based on a renaissance of the Hebrew language and culture and on the Jewish movement for Political rebirth (Zionist movement). It was not uniform and could be divided into: — Utarquist tendenciesa)Polish/Hebrew (Social Association schools, Mizrahi schools)b)Jewish/Hebrew— a radical Hebrew tendency within the central Tarbut organization.Secondary schoolsThe great majority of Jewish religious youth attended public secondary schools, apart from which there were private schools, many of them only for Jewish youth. With time the number of Yiddisch language schools decreased, while the number of schools with Polish- nad Hebrewlanuage instruction increased: where in addition to compulsory secular subjects offered in Polish, Jewish subjects in Hebrew were introduced on a larger scale. In the school year 1938/39 there were 81 private Jewish middle schools in Poland, with Polish as the language of instruction, among which 67 were certified as public schools, and 66 high schools, including 42 certified as public high schools.Vocational schoolsThe picture of Jewish students would be incomplete without vocational schools. Private vocational schools that prepared young people for emigration to Palestine were organized. Special social organizations were created, supported by foreign and Polish foundations for the development of Jewish vocational schools. Among the leading organizations were:The Society for Support of Agriculture and Crafts (ICA);The Society for the Promotion of Technical and Agricultural Work among Jews in Poland (ORT); andThe Association for Promoting Education among Jews in Małopolska (Wuzet).The extracurricular institutions that were created to support vocational schools, were often conted as vocational and technical training institutions. There were also vocational schools providing courses for young employees, for whom vocational training was compulsory until the age of 18. Typically, Jewish youth met that obligation not by attending private schools; the great majority went to the public schools that provided additional education to all youth.One cannot ignore the role of numerous organizations which, out of concern for the adolescents, made efforts to facilitate acquisition of vocational qualifications for them and at the same time encouraged them to join their organizations and to win them to their political viewpoints. The Zionist organizations were also active. The most powerful organization of this kind was the Hechalutz youth organization, established in 1920, with a membership of about 12,000 young people in several hundred provincial divisions.III. Jewish schools in CracowDuring the Second Republic of Poland there were two groups of elementary schools for Jewish children in Cracow.Public shools: Kazimierz the Great school no. 5 at 3/5 Wąska Street; Józef Ignacy Kraszewski School No. 8 at 36 Miodowa Stret; Mikołaj Rej School No. 14 at 2 Dietla Street; Klementyna Tański Hoffmanowa School No. 15 at 36a Miodowa Street; and Jan Długosz School, No. 22 at 7 Wąska Street, belonged to the first group.The second group were private elementary schools run by Orthodox organizations — Talmud Torah at 6 Estery Street; Talmud Torah II at 30 Rękawka Stret; and the orthodox Yesodai Hatorah School at 64 Dietla Street.The Ivri Heder at 26 Miodowa Street, where the Tahkeomi seconadry school for boys was open in addition to an elementary school for boys, was the only school in Poland in its kind to join general knowledge and modern public education with Jewish learning in the spirit of faith and tradition. In 1936/37 the Ivri Heder Society opened a one-year Commercial School for youth aged 13 to 18. The Jewish Coeducational Community and High School, Haim Hilfstein Hebrew Secondary School at 5 Brzozowa Street, added the building at 3 Brzozowa Street, and in 1930 a third building at 8 and 10 Podbrzezie Street. The Bet-Hamidrash-Nahlat Avot school prayer house, created at the initiative of the students themselves, was located there.The Private Crafts School of the Jewish Society for Community and Secondary Schooling was housed initially at 5 Brzozowa Street on the ground floor and in the basement; in 1937-1938 a new two-storey building at 3 Podbrzezie street was constructed, to house the Crafts School exclusively. In 1938 the school authorities decided to turn it into the three-year Private Mens’ High School of Mechanics.The Private Jewish Coeducational High School of Commerce at 10 Stradomska Street. In line with the reorganization of the school system and the obligation to reform vocational schools into high schools, in 1938/39 the school began to operate as the Private Jewish Coeducational Commercial High School at the Cracow Merchant Association. Thanks to the Association’s efforts, the Coeducational College of Administration was opened on October 3, 1938, for high school graduates.There were also two vocational schools for girls only.One was the Private Vocational High School for Jewish Girls at the Ognisko Pracy Society. From 1936 the school was housed in a modern four-storey building at 7 Skawińska Boczna Street. The second was a Bet Yakov school from which the Bet-Yakov movement for girls’ education began. From 1929 the school had at its disposal a four-storey building at 10 Stanisława Street.In addition to those there were also:The High School for Girls at the Jewish New School Society, at 1 Starowiślna Street. In 1937/38 the Coeducational High School at the Jewish Society for Community School at 17 Main Market Square;Private College for Girls, teaching religion and housekeeping, in Paulińska Street;Private School of Dance Exercise and Fine Arts;Special school for mentally disabled children, at 7 Wąska Street.When the Germans unleashed the Second World War, the fate of the Jewish people in Poland was decided. Soon after the beginning of the occupation, repression against Jewish religion teachers and youth started. On December 11, 1939, the Jewish schools were eliminated by order of the Cracow district governer Wachter.